Implementasi Pembiayaan Modal Kerja BMT Artha Yappi Dalam Meningkatkan UMKM Putra Tambak Rejo Furniture Jepara - Syarifatul Wardah; Wahidullah; Ahmad Fauzan Mubarok (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This study aims to analyze the role of working capital financing provided by BMT Artha Yappi in improving the performance of Putra Tambak Rejo Furniture as a Micro, Small, and Medium Enterprise (MSME) in the furniture sector. The method used a descriptive qualitative approach and case study design, with data collected through in-depth interviews, participatory observation, and documentation studies. The results of the study show that working capital financing of IDR 40 million with a Murabahah contract was effectively allocated for the purchase of modern sanding machines and additional raw materials. The implementation of this financing had a significant impact on improving business performance, as evidenced by a 50% increase in production capacity (from 10 to 15 sets/month) and a 40% increase in monthly turnover (from IDR 50 million to IDR 70 million). This success was not only driven by capital factors, but also reinforced by the role of BMT Artha Yappi in providing intensive technical and managerial assistance.